1865-66 N.C. Sess. Laws 103-04 - (:unkn) unknown (My University, 1866)
Pub Laws, ch. 40, § 15: "an act to amend chapter one hundred and seven, section sixty-six, of the Revised Code, relating to free negroes having arms;
Keywords: ENSLAVED PERSONS & OTHER MINORITIES